Nano-sized iron particles may induce multiple pathways of cell death following generation of mistranscripted RNA in human corneal epithelial cells. (August 2017) - Park, Eun-Jung; Chae, Jae-Byoung; Kang, Seuyoung; Lyu, Jungmook; Jeong, Uiseok; Yeom, Changjoo; Kim, Younghun; Chang, Jaerak
Abstract: Iron is closely associated with an ambient particulate matters-induced inflammatory response, and the cornea that covers the front of the eye, is among tissues exposed directly to ambient particulate matters. Prior to this study, we confirmed that nano-sized iron particles (FeNPs) can penetrate the cornea. Thus, we identified the toxic mechanism of FeNPs using human corneal epithelial cells. At 24 h after exposure, FeNPs located inside autophagosome-like vacuoles or freely within human corneal epithelial cells. Level of inflammatory mediators including nitric oxide, cytokines, and a chemokine was notably elevated accompanied by the increased generation of reactive oxygen species. Additionally, cell proliferation dose-dependently decreased, and level of multiple pathways of cell death-related indicators was clearly altered following exposure to FeNPs. Furthermore, expression of gene encoding DNA binding protein inhibitor (1, 2, and 3), which are correlated to inhibition of the binding of mistranscripted RNA, was significantly down-regulated. More importantly, expression of p-Akt and caspase-3 and conversion to LC3B-II from LC3B-I was enhanced by pretreatment with a caspase-1 inhibitor. Taken together, we suggest that FeNPs may induce multiple pathways of cell death via generation of mistranscripted RNA, and these cell death pathways may influence by cross-talk. Furthermore, we propose the need of further study for the possibility of tumorigenesis following exposure to FeNPs. Highlights: We studied toxicity of iron nanoparticles (FeNPs) in human corneal epithelial cells. FeNPs located freely in the cells or within autophagosome-like vacuoles. FeNPs inhibited cell proliferation with an increase of inflammatory mediators. FeNPs altered expression of multiple pathways of cell death-related proteins. Generation of mistranscripted RNA and immature cells are suggested as a cause.